1944
DOI: 10.1152/ajplegacy.1944.141.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ion Movement Between the Intestinal Lumen and the Blood

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1945
1945
1971
1971

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…Goldschmidt and Dayton (1) showed that NaC1 entered the colon of dogs from the blOod, and a number of investigators have observed that water moves relatively freely, since it is absorbed rapidly from hypotonic solutions placed in the intestine but enters hypertonic solutions. Visscher et al (2,3) using radioactive Na and C1 and D~O as tracers confirmed and extended these earlier results. More recently, absorption of NaC1 and water has been studied by Bucher, Anderson, and Robinson (4), D'Agostino, Leadbetter, and Schwartz (5), Budolfsen (6), Goldman et al (7), and Wilson (8).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Goldschmidt and Dayton (1) showed that NaC1 entered the colon of dogs from the blOod, and a number of investigators have observed that water moves relatively freely, since it is absorbed rapidly from hypotonic solutions placed in the intestine but enters hypertonic solutions. Visscher et al (2,3) using radioactive Na and C1 and D~O as tracers confirmed and extended these earlier results. More recently, absorption of NaC1 and water has been studied by Bucher, Anderson, and Robinson (4), D'Agostino, Leadbetter, and Schwartz (5), Budolfsen (6), Goldman et al (7), and Wilson (8).…”
mentioning
confidence: 56%
“…(2,3) in the small intestine of the dog. Furthermore, there was often a considerable variation in flux from one period to another in the same animal.…”
Section: (21)mentioning
confidence: 99%
“…A blind end Thiry fistula was prepared and the continuity of the bowel reestablished (8,9). In a pair of experiments on the ileum radiosodium was first placed in the lumen of the bowel and in the second experiment it was administered intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Inulin was used to follow the volume of fluid in the bowel and the amount of sodium in the bowel was calculated from the known amount of inulin in the bowel, and from measurements of the inulin and sodium concentrations (Table I). ~ When the amount of sodium in the bowel was plotted on (1) an arithmetic scale and s Visscher in 1944 conducted experiments similar to those described above (9). In his calculations he used the decrease in the total number of labelled ions as a measure of the rate out of the bowel.…”
Section: An Experimental Appticogion Of T~ Deriv~ Equationsmentioning
confidence: 99%
See 1 more Smart Citation